VISUAL CULTURAL DIFFERENCES OF SOUTHERN AND NORTHERN WATER TRIBE WOMEN IN AVATAR: THE LAST AIRBENDER - Saleh, Muhammad Rafi Adira; Prakoso, Stormy Yudo (Institut Seni Indonesia Padangpanjang, 2025)
Animation media has a role in the process of global cultural exposure, especially through the designed worldbuilding in it. An animated work with worldbuilding that designs culture well is the animated series Avatar: The Last Airbender. This research is focused on exploring the differences between the cultures of the Southern and Northern Water Tribes in the world of Avatar based on Hofstede's four layers of cultural theory (Symbols, Heroes, Rituals, & Values), especially in women's culture. The research was conducted using comparative qualitative methods. In this research, differences were found in Symbols (clothing, hair, jewelry), Heroes (Katara and Yue), Rituals, and Values in the two water tribes. Southern women prioritize practicality and survival, as reflected by Katara while northern women emphasize social order and tradition, embodied by Princess Yue. This research shows that in worldbuilding, various cultures can be formed and deepen the narrative of an animation.